Differences in incidence and survival of oral cavity and pharyngeal cancers between Germany and the United States depend on the HPV-association of the cancer site. (January 2018) - Jansen, L.; Buttmann-Schweiger, N.; Listl, S.; Ressing, M.; Holleczek, B.; Katalinic, A.; Luttmann, S.; Kraywinkel, K.; Brenner, H.; ,
Highlights: Survival after HPV-related oral cavity and pharynx cancer was higher in the US. These differences were only observed in men and increased over time. Differences were largest for younger patients and patients with stage IV disease. Survival was comparable in Germany and the US at HPV-unrelated sites. Abstract: Introduction: The epidemiology of squamous cell oral cavity and pharyngeal cancers (OCPC) has changed rapidly during the last years, possibly due to an increase of human papilloma virus (HPV) positive tumors and successes in tobacco prevention. Here, we compare incidence and survival of OCPC by HPV-relation of the site in Germany and the United States (US). Materials and methods: Age-standardized and age-specific incidence and 5-year relative survival was estimated using data from population-based cancer registries in Germany and the US Surveillance Epidemiology and End Results (SEER) 13 database. Incidence was estimated for each year between 1999 and 2013. Relative survival for 2002–2005, 2006–2009, and 2010–2013 was estimated using period analysis. Results: The datasets included 52, 787 and 48, 861 cases with OCPC diagnosis between 1997 and 2013 in Germany and the US. Incidence was much higher in Germany compared to the US for HPV-unrelated OCPC and more recently also for HPV-related OCPC in women. Five-year relative survival differences between Germany and the US were small for HPV-unrelated OCPC. For HPV-related OCPC, men had higher survival in the US (62.1%) than in Germany (45.4%) in 2010–2013. These differences increased over time and were largest in younger patients and stage IV disease without metastasis. In contrast, women had comparable survival for HPV-related OCPC in both countries. Conclusions: Strong survival differences between Germany and the US were observed for HPV-related OCPC in men, which might be explained by differences in HPV-attributable proportions. Close monitoring of the epidemiology of OCPC in each country is needed.